2020
DOI: 10.1002/smll.202002229
|View full text |Cite
|
Sign up to set email alerts
|

Folding at the Microscale: Enabling Multifunctional 3D Origami‐Architected Metamaterials

Abstract: Mechanical metamaterials inspired by the Japanese art of paper folding have gained considerable attention because of their potential to yield deployable and highly tunable assemblies. The inherent foldability of origami structures enlarges the material design space with remarkable properties such as auxeticity and high deformation recoverability and deployability, the latter being key in applications where spatial constraints are pivotal. This work integrates the results of the design, 3D direct laser writing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…Some auxetic systems are also characterised by a negative value of the coefficient of thermal expansion, implying that they shrink when subjected to an increase in temperature [33][34][35]. Additionally, it has been shown that it is also possible to achieve a smooth transition through a wide range of negative and positive Poisson's ratios by using an origami cell that morphs continuously between a Miura mode and an eggbox mode [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Some auxetic systems are also characterised by a negative value of the coefficient of thermal expansion, implying that they shrink when subjected to an increase in temperature [33][34][35]. Additionally, it has been shown that it is also possible to achieve a smooth transition through a wide range of negative and positive Poisson's ratios by using an origami cell that morphs continuously between a Miura mode and an eggbox mode [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Last, we demonstrate the drug storage and release capabilities of the crawler by using the inherent internal cavity of the Kresling unit. To expand the work, advanced fabrication methods, such as small-scale three-dimensional printing ( 49 ), stress-controlled folding ( 50 ), and mechanically guided assembly ( 51 ), can further downsize the origami crawler, bringing forth potential applications in more narrow and confined environments. Highly autonomous biomedical robots based on the presented design are promising for future disease diagnoses and treatment by integrating the functionalities of sensing, vision, computing, and drug storage into the Kresling origami internal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The method is seen to produce freely movable microstructures made of mechanical metamaterials and exhibited NPRs of as low as -0.44 [140]. Three-dimensional origami structures with appreciable foldability were fabricated using DLW [141]. The easier foldability is attributed to the reduced bending stiffness at the micro-and nano-dimensions.…”
Section: Dlwmentioning
confidence: 99%